Business Cycles and Equilibrium. - Siegel, Jeremy J.; Black, Fischer (Journal of Finance, 1988)
Foreword. Introduction. Chapter 1: Banking and Interest Rates in a World Without Money: The Effects of Uncontrolled Banking. Chapter 2: Active and Passive Monetary Policy in a Neoclassical Model. Chapter 3: Rational Economic Behavior and the Balance of Payments. Chapter 4: Uniqueness of the Price Level in Monetary Growth Models with Rational Expectations. Chapter 5: Purchasing Power Parity in an Equilibrium Model. Chapter 6: Ups and Downs in Human Capital and Business. Chapter 7: How Passive Monetary Policy Might Work. Chapter 8: What a Non-Monetarist Thinks. Chapter 9: Global Monetarism in a World of National Currencies. Chapter 10: The ABCs of Business Cycles. Chapter 11: A Gold Standard with Double Feedback and Near Zero Reserves. Chapter 12: The Trouble with Econometric Models. Chapter 13: General Equilibrium and Business Cycles. Chapter 14: Noise. Index.